Is Bitcoin a relevant predictor of standard & poor's 500? - Camilla Muglia; Luca Santabarbara; Stefano Grassi (Journal of Risk and Financial Management, 2019)
The paper investigates whether Bitcoin is a good predictor of the Standard & Poor's 500 Index. To answer this question we compare alternative models using a point and density forecast relying on Dynamic Model Averaging (DMA) and Dynamic Model Selection (DMS). According to our results, Bitcoin does not show any direct impact on the predictability of Standard & Poor's 500 for the considered sample.
Keywords: 330; cryptocurrency; Bitcoin; forecasting; point forecast; density forecast; dynamic model averaging; dynamic model selection; forgetting factors